One-step fabrication of hollow-channel gold nanoflowers with excellent catalytic performance and large single-particle SERS activity. Issue 32 (28th June 2016) - Ye, Sunjie; Benz, Felix; Wheeler, May C.; Oram, Joseph; Baumberg, Jeremy J.; Cespedes, Oscar; Christenson, Hugo K.; Coletta, Patricia Louise; Jeuken, Lars J. C.; Markham, Alexander. F.; Critchley, Kevin; Evans, Stephen D.
Abstract : Hollow-channel gold nanoflowers are fabricated via a one-step synthesis using an auto-degradable nanofiber as a bifunctional template. Abstract : Hollow metallic nanostructures have shown potential in various applications including catalysis, drug delivery and phototherapy, owing to their large surface areas, reduced net density, and unique optical properties. In this study, novel hollow gold nanoflowers (HAuNFs) consisting of an open hollow channel in the center and multiple branches/tips on the outer surface are fabricated for the first time, via a facile one-step synthesis using an auto-degradable nanofiber as a bifunctional template. The one-dimensional (1D) nanofiber acts as both a threading template as well as a promoter of the anisotropic growth of the gold crystal, the combination of which leads to the formation of HAuNFs with a hollow channel and nanospikes. The synergy of favorable structural/surface features, including sharp edges, open cavity and high-index facets, provides our HAuNFs with excellent catalytic performance (activity and cycling stability) coupled with large single-particle SERS activity (including ∼30 times of activity in ethanol electro-oxidation and ∼40 times of single-particle SERS intensity, benchmarked against similar-sized solid gold nanospheres with smooth surfaces, as well as retaining 86.7% of the initial catalytic activity after 500 cycles in ethanol electro-oxidation). This innovative synthesis gives a nanostructure of the geometry distinct from the template and is extendable to fabricating other systems for example, hollow-channel silver nanoflowers (HAgNFs). It thus provides an insight into the design of hollow nanostructures via template methods, and offers a versatile synthetic strategy for diverse metal nanomaterials suited for a broad range of applications.